Keynesian economics : the search for first principles - Coddington, Alan, 1941-1982 (Routledge library editions. Economics series., 2003)
Keynesian Economics provides a wide-ranging critical examination of the presuppositions and procedures of Keynesian analysis. The result is both a clear guide to modern macro-economic theory and policy and a revealing exercise in the recent history of ideas - ideas which are highly contentious and still deeply influential.""(Alan) Coddington made several substantive contributions to the understanding of Keynesian economics which established his fame not merely in the UK but in major centres of economics around the world."" The Times